Analytical fragility curves of shallow-founded structures subjected to Soil-Structure Interaction (SSI) effects. Issue 141 (February 2021) - Forcellini, Davide
Abstract: Soil structure interaction (SSI) may affect significantly the seismic vulnerability of structures with several mechanisms that depend on the mutual effects of soil properties and structural characteristics. A probabilistic-based approach is here applied to evaluate the effects of SSI on the fragility assessment of two selected benchmark buildings: a Reinforced Concrete with Infill Masonry Walls (RCIMW) and a Reinforced Concrete (RC). Analytical fragility curves were developed by performing non-linear 3D numerical simulations with Opensees that implements hysteretic materials and advanced plasticity models for representing non-linear soil conditions and structural configurations. The effects of soil deformability and structural flexibility on the non-linear response of the system (soil-foundation-structure) were assessed and discussed by referring to four limit states (slight, moderate, extensive and collapse) with respect to the maximum inter storey drifts. Highlights: Soil structure interaction. Analytical fragility curves. 3D Numerical simulations. Opensees. Non-linearity.